“Extrauterine growth restriction” and “postnatal growth failure” are misnomers for preterm infants (2020)
Preterm infants are increasingly diagnosed as having“extrauterine growth restriction”(EUGR) or“postnatal growth failure”(PGF). Usually EUGR/PGF is diagnosed when weight is <10th percentile at either discharge or 36–40 weeks postmenstrualage. The reasons why the phrases EUGR/PGF are unhelpful include, they: (i) are not predictive of adverse outcome; (ii) arebased only on weight without any consideration of head or length growth, proportionality, body composition, or geneticpotential; (iii) ignore normal postnatal weight loss; (iv) are usually assessed prior to growth slowing of the reference fetus,around 36–40 weeks, and (v) are usually based on an arbitrary statistical growth percentile cut-off. Focus on EUGR/PGFprevalence may benefit with better attention to nutrition but may also harm with nutrition delivery above infants’actualneeds. In this paper, we highlight challenges associated with such arbitrary cut-offs and opportunities for further refinementof understanding growth and nutritional needs of preterm neonates